2021
DOI: 10.3389/frvir.2021.716318
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Fear Responses in Virtual Reality: A Mobile EEG Study on Affective, Behavioral and Electrophysiological Correlates of Fear

Abstract: Fear is an evolutionary adaption to a hazardous environment, linked to numerous complex behavioral responses, e.g., the fight-or-flight response, suiting their respective environment. However, for the sake of experimental control, fear is mainly investigated under rather artificial laboratory conditions. The latter transform these evolutionary adaptions into artificial responses, like keystrokes. The immersive, multidimensional character of virtual reality (VR) enables realistic behavioral responses, overcomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 105 publications
4
33
0
Order By: Relevance
“…This analysis showed that 23 participants were necessary to achieve a power of 0.80. Our group sample size is greater than that of Schöne et al (2016), who displayed images to participants while investigating FAA through EEG, and similar to Kisker et al (2021), who used EEG to investigate FAA during an immersive VR experience. Participants received a 10 United States dollar Amazon gift card as compensation.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis showed that 23 participants were necessary to achieve a power of 0.80. Our group sample size is greater than that of Schöne et al (2016), who displayed images to participants while investigating FAA through EEG, and similar to Kisker et al (2021), who used EEG to investigate FAA during an immersive VR experience. Participants received a 10 United States dollar Amazon gift card as compensation.…”
Section: Participantsmentioning
confidence: 99%
“…Numerous studies have investigated affective responses to better understand user emotions elicited during various VR experiences. Affective responses in VR have been investigated through self-reported data (Felnhofer et al, 2015;Lin, 2017;Voigt-Antons et al, 2021) as well as physiological data (Kerous et al, 2020;Kisker et al, 2021;Schöne et al, 2021). Self-reported data often examines affect from the perspective of a dimensional model of affect (Poria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To compare responses between conditions, the authors conducted a repeated-measures ANOVA test. Kisker et al [ 16 ] gathered electrophysiological correlates of fear and avoidance tendencies from EEG signals. Subsequently, Shapiro–Wilk tests were used to check the normality of the variables.…”
Section: Introductionmentioning
confidence: 99%